Hidden efficiencies: On the relevance of business justifications in abuse of dominance cases - Hans W. Friederiszick; Linda Gratz (European School of Management and Technology (ESMT), 2013)
This article assesses the relevance of efficiencies and other justifications in recent Article 102 TFEU cases. Based on a review of all EU decisions and openings between 2009 and mid 2013 we find that procompetitive justifications still play a mediocre role in the EU Commission's evaluations, except in IT related abuse cases. This stands in contrast to the policy goals expressed during the reform phase (2005 to 2009), the Guidance Paper and the increasing relevance of efficiency considerations in merger proceedings. We argue that this is due to a malfunctioning of the balancing test, i.e., the weighting of pro- and anticompetitive effects, as pro- and anticompetitive effects are often non-separable and non-monotone in Article 102 TFEU cases. In addition, the increasing practice of commitment decisions reduces transparency; little guidance regarding dynamic efficiencies further diminishes the relevance of business justifications in Article 102 TFEU cases. Policy options are discussed.
urn:nbn:de:101:1-2013091111529
Keywords: K21; L21; L40; 650; European competition policy; abuse of dominance; efficiency defense